From the “Siren’s Song” to the Noise of Sirens - Feitosa, Charles (Revista Brasileira de Estudos da Presença, 2025)
The aim of this essay is to explore the conceptual and cultural transformations of the voice, based on the possible relations between the classic account of the sirens’ song and the modern advent of sirens, artifacts used mainly to warn populations of imminent disasters. The hypothesis is that both in the traditional account of the sirens/mermaids and in the technical conception of sirens there is a devaluation of sound in favor of speech. Finally, some ways of re-signifying the sirens’ song are suggested, based on a conceptual matrix that avoid the hierarchical opposition between meaning and senses.